LEGAL-SOCIO PEMILIHAN KEPALA DAERAH DAN WAKIL KEPALA DAERAH SERENTAK DI MASSA PANDEMI COVID-19 - Muthowif, Muthowif; Sofiyah, Siti Lailatus (Universitas Wijaya Kusuma Surabaya, 2021)
The election of Governors and Deputy Governors, Regents and Deputy Regents, as well as Mayors and Deputy Mayors throughout Indonesia which was held on December 9, 2020, and is the fourth simultaneous regional election held in Indonesia. During the COVID-19 pandemic, it is a continuation of the simultaneous regional head elections in conditions of non-natural disasters which were originally planned to be held on September 23, 2020. The research method is normative juridical and normative-empirical (applied) legal research. This research focuses on the study of the application of the rules or norms in positive law with a sociological approach. To avoid the spread of covid-19, in the implementation of the follow-up elections in the non-natural disaster conditions Covid-19 in 2020, then in accordance with article 8C paragraph 1, General Election Commission Regulation number 5 of 2020 concerning the third amendment to General Election Commission regulation number 15 of 2020 regarding the stages, programs and schedules for organizing the elections for the Governor and Deputy Governor, Regent and Deputy Regent, and/or mayor and Deputy Mayor in 2020, that all stages, programs, and schedules for further simultaneous elections must be carried out with a health protocol for handling Covid-19 , both at the KPU, Bawaslu, and DKPP levels.Â Keywords: General Election, Regional Head, Covid-19 Pandemic, KPU, Bawaslu, DKPP